2009
DOI: 10.1111/j.1570-7458.2008.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Spring temperature and precipitation affect tobacco thrips, Frankliniella fusca, population growth and Tomato spotted wilt virus spread within patches of the winter annual weed Stellaria media

Abstract: Effects of temperature and rainfall timing, amount, and duration on the spread of Tomato spotted wilt virus (Bunyaviridae: genus Tospovirus; TSWV) and population growth of its primary vector, Frankliniella fusca (Hinds) (Thysanoptera: Thripidae), within patches of common chickweed, Stellaria media (L.) Cyrillo (Caryophyllaceae), were examined during the spring of 2004, 2005, and 2006. Elevated temperature treatments were investigated in an attempt to alter the age structure of F. fusca populations and change t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…The tobacco thrips might be also an incidental visitor to tobacco fields. Our findings support that TSWV occurrences in tobacco fields mainly depend on immigration of macropterous adults of tobacco thrips produced on host plants other than tobacco in the spring after tobacco planting [16], because the tobacco thrips exhibits wing dimorphism and brachypters are not able to fly. Only brachypters of tobacco thrips occurred at moderate and lower temperature conditions below 18˚C on green bean leaves, though it is known that higher temperatures induce production of macropterous females [17].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The tobacco thrips might be also an incidental visitor to tobacco fields. Our findings support that TSWV occurrences in tobacco fields mainly depend on immigration of macropterous adults of tobacco thrips produced on host plants other than tobacco in the spring after tobacco planting [16], because the tobacco thrips exhibits wing dimorphism and brachypters are not able to fly. Only brachypters of tobacco thrips occurred at moderate and lower temperature conditions below 18˚C on green bean leaves, though it is known that higher temperatures induce production of macropterous females [17].…”
Section: Discussionsupporting
confidence: 74%
“…On other plants including tomato and pepper, Capsicum annuum L., it has been mentioned that they can maintain population. In addition, cultures of F. fusca can be kept on green bean pods and whole green bean plant, [11] [12] [14]- [16]. However, no life history parameters on green bean have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groves et al (2002), through sampling adults and immatures from winter weeds and rearing immatures to adulthood on green bean (Phaseolus vulgaris L.) pods, demonstrated that winter weeds could serve as hosts of F. fusca. Other Þeld studies indicated that the winter weeds differed in their abilities to support thrips populations (Groves et al 2001, Morsello andKennedy 2009). However, biological Þtness parameters of F. fusca on various winter weeds over an entire generation (adult to adult) were not exclusively studied in the laboratory.…”
mentioning
confidence: 94%
“…General patterns of thrips dispersal can be related to regional temperature and precipitation that inßu-ence generation turn-over, ßight, and mortality (e.g., Davidson and Andrewartha 1948, Harding 1961, Kirk 1997, Lewis 1997, Lowry et al 1992, Morsello et al 2010, Morsello and Kennedy 2009. However, farm-scale variation in thrips populations and adult dispersal also are affected by local factors, which include host plant availability and suitability (Davidson and Andrewartha 1948).…”
mentioning
confidence: 97%